Autoethnographic Reflections on Navigating the Path to Empower Teachers’ Transversal Skills - Dahal, Rajendra (Journal of Transformative Praxis, 2023)
This inquiry portrays my experiences in enhancing teachers’ transversal skills. As our national curriculum changed in 2019, my primary concern shifted to developing learners’ transversal skills, but I was not aware of the way towards it. While working as a teacher educator, I could find teachers and teacher educators neglecting learners’ transversal skills. Somehow, I have observed similar practices in my facilitation as well. As per the national curriculum on school education, teachers need to facilitate learners in such a way that contributes to developing learners’ transversal skills (CDC, 2019, 2020, 2021a, 2021b). But without developing the transversal skills of teachers, can we develop the transversal skills of students? This question led me to observe my practices and practices of teachers. While going to my flash bag, I found that I primarily used a teacher-centered facilitation method similar to other teachers.. Studying STEAM at University became a turning point in my professional career where I felt a shift in my profession and this event became a pathway to shift my paradigm. I have used a multi-paradigmatic research design to present my shift and unfold my experiences. I have extended the investigation agenda using autoethnography and have introduced a sequence of lived experiences and discussions to highlight significant changes. I have completed my inquiry using the theory of transformative learning, constructivist learning, and STEAM-based pedagogical lens. The finding of this inquiry reveals that transversal skills can be developed through following the lens of STEAM education. We can create innovative pedagogy like "3C-R," which I have started by adding theories into practices.